Girl with a voice: Bana Alabed's digital engagement and democratic practice. Issue 5 (2nd September 2020) - Hauge, Chelsey
ABSTRACT: This article addresses how one girl uses social media to document her experience of the Syrian war. She contends that making sense of her networked media participation through the frame of democratic practice offers a way of understanding youth culture that moves beyond narratives of agency. Drawing on Sarah Ahmed's recent work, I consider the sticky quality of Bana Alabed's twitter posts, arguing that she is both Bana Alabed the embodied girl, and Bana Alabed the cultural construction as filtered through and made sticky by her girlhood. I address the contemporary climate surrounding media, girlhood, and difference in order to argue that Bana's writing – both on Twitter and in her book, Dear World – constitute what Muñoz or Ranciere might call democratic practice.